Identification of CLEC10A as a human lectin for pancreatic ductal adenocarcinoma - Shuntaro Tsukamoto; Hiroaki Tateno; Osamu Shimomura; Kana Yamamoto; Sayoko Saito; Jinko Murakami; Hiromitsu Nakahashi; Yoshihiro Miyazaki; Tsuyoshi Enomoto; Tatsuya Oda (Scientific Reports)
Abstract The mechanism by which glycans in pancreatic ductal adenocarcinoma (PDAC) interact with human endogenous lectins in the tumor microenvironment remains largely unknown. This study aimed to identify endogenous lectins that recognize and bind to pancreatic ductal adenocarcinomas. The reactivity of 43 human endogenous lectins belonging to the Galectin, Siglec, and C-type lectin families in PDAC cell lines and clinical PDAC samples was analyzed using flow cytometry and immunostaining of tissues. C-type lectin domain family 10 member A (CLEC10A), a C-type lectin, was a candidate endogenous lectin with high reactivity in some pancreatic cancer cells. CLEC10A lectin bound in approximately 60% of 113 clinical pancreatic cancer tissue sections. Immunohistochemistry with anti-CLEC10A antibody showed that CLEC10A was mainly expressed in CD163-positive monocytic cells. Of the 57 patients (out of 113) who achieved R0 surgical resection at stage II/III, those with high CLEC10A expression on macrophages and CLEC10A ligand expression on PDAC cells had significantly shorter overall survival. CLEC10A is a human lectin receptor for pancreatic ductal adenocarcinoma. The coexistence of CLEC10A-expressing cells in pancreatic cancer tissues and CLEC10A ligands on pancreatic cancer cells indicates poor prognosis.